Pengembangan Produk Ijarah Sebagai Alternatif Pembiayaan di Lembaga Keuangan Syariah: Tinjauan Terhadap Implementasi di Indonesia - Nala Amalia; Nur Amelia; Berliana Putri; Mohd. Winario (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
This study aims to examine the development of Ijarah products as an alternative financing in Islamic Financial Institutions (LKS) in Indonesia, with a focus on its implementation in meeting customer financing needs. Ijarah, as a lease agreement in the Islamic financial system, offers financing solutions that are in accordance with sharia principles and has great potential in the Indonesian Islamic financial industry. This study uses a qualitative method with a case study approach, analyzing primary and secondary data from several LKS that have implemented Ijarah products. The research findings show that Ijarah products have advantages in providing financing flexibility, especially in fixed asset sectors such as property and vehicles. However, challenges faced in developing this product include a lack of customer understanding and regulatory complexity. The implications of this study indicate that strengthening socialization and increasing the operational capacity of LKS in offering Ijarah products is very important to increase the competitiveness and inclusion of Islamic finance in Indonesia.